Electrochemical preparation method of adiponitrile

By doping Bi elements and adding corrosion inhibitors such as lauramide in acrylonitrile electrolytic dimerization, the problem of frequent electrode corrosion and replacement is solved, and efficient preparation and production cost of adiponitrile is achieved.

CN119776854AInactive Publication Date: 2025-04-08WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311280608.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-07
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the acrylonitrile electrolytic dimerization method has severe electrode corrosion and frequent electrode replacement, resulting in high production costs.

Method used

Adipiconet was electrochemically prepared by doping Bi elements on the surface of the cathode electrode and adding lauramide and its derivatives to the electrolyte as cathode corrosion inhibitor.

Benefits of technology

It effectively reduces the loss rate of cadmium and lead on the cathode surface, extends the electrode life, reduces production costs, and improves product selectivity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an electrochemical preparation method of adiponitrile, which inhibits corrosion of bismuth, lead and cadmium on the surface of a cathode by introducing lauramide and derivatives thereof as a cathode corrosion inhibitor, and solves the problems that lead and cadmium rapidly corrode and fall off on the surface of the cathode in the traditional synthesis process and an electrolytic bath needs to be frequently replaced in the production process. And the method also has the advantages of improving the selectivity of generating adiponitrile through acrylonitrile dimerization and reducing side reactions, and is suitable for wide industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adiponitrile preparation, and in particular to an electrochemical preparation method of adiponitrile. Background Art

[0002] Adiponitrile (ADN), also known as 1,4-dicyanobutane, has a molecular formula of NC(CH2)4CN and is an important organic chemical raw material. The most important use of adiponitrile is the production of hexamethylenediamine, which reacts with adipic acid to produce nylon 66 salt, and then produces nylon 66 fiber. About 90% of the world's adiponitrile is used for the production of nylon 66 salt each year, and the cost of adiponitrile accounts for about 40% of the production cost of nylon 66 salt. In addition, hexamethylenediamine can also be used to obtain HDI (1,6-diisocyanate) through photochemical reaction, and HDI is the main raw material for the production of high-end environmentally friendly coatings, which is another important use of adiponitrile.

[0003] The industrial production process of adiponitrile mainly includes adipic acid ammoniation dehydration method, acrylonitrile electrolytic dimerization method and butadiene hydrocyanation method. Among them, the adipic acid ammoniation dehydration method has complex process, high raw material cost, low product yield and poor quality, and has been eliminated abroad; although the butadiene hydrocyanation method has low raw material cost, mature process and advanced technology, hydrocyanic acid is a highly toxic substance with huge potential risks, long reaction process and high technical barriers, and it is very difficult to develop this method in my country. Compared with the adipic acid method and the butadiene method, the biggest advantage of the acrylonitrile electrolytic dimerization method is that the reaction process is simple and the raw materials are cheap and easy to obtain. During the electrolytic reaction, an oxidation reaction occurs at the anode to provide free electrons, and acrylonitrile dimerizes at the cathode to generate adipic acid. At present, the cathode of electrolytic acrylonitrile mainly uses lead and cadmium, but the cathode has the main problems of low product selectivity, severe corrosion of lead and cadmium at the cathode, and frequent replacement of the cathode in the electrolytic cell.

[0004] How to create a new electrochemical preparation method of adiponitrile so as to slow down electrode corrosion, reduce the frequency of electrode replacement, and thus reduce production costs is of great positive significance. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides an electrochemical preparation method of adiponitrile, which can effectively solve the problem of rapid loss of cadmium and lead on the cathode surface. At the same time, bismuth doping at the cathode can catalyze the dimerization of acrylonitrile and improve product selectivity.

[0006] To achieve the above object, the present invention is implemented through the following technical solutions:

[0007] An electrochemical preparation method of adiponitrile, the method is carried out in a diaphragm-free electrolytic cell, and the steps include:

[0008] S1: uniformly mix acrylonitrile, quaternary ammonium base, EDTA, lauramide and its derivatives, supporting electrolyte and water to prepare an electrolytic raw material solution, and inject it into the electrolytic cell;

[0009] S2: Pass current into the electrolytic cell to carry out electrolysis reaction.

[0010] Preferably, in step S2, acrylonitrile is added to the electrolytic cell to maintain the acrylonitrile concentration in the electrolyte.

[0011] In step S1 of the preparation method of the present invention, the mass percentage of acrylonitrile in the electrolytic raw material solution is 0.5-5%, for example, 1%, 2%, 3%, 4%, 5%, preferably 1-3%; preferably, the quaternary ammonium base is one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide, and the mass percentage of the acrylonitrile in the electrolytic raw material solution is 0.5-3%, preferably 1-2%;

[0012] Preferably, the mass percentage of EDTA in the electrolyte raw material solution is 0.1-1%, such as 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, preferably 0.3-0.5%;

[0013] Preferably, the lauramide and its derivatives include one or more of lauramide, N-[3-(dimethylamino)propyl]lauramide, and N,N-diethyllauramide.

[0014] The mass percentage of lauramide and its derivatives in the electrolyte raw material solution is 1-5%, such as 2%, 3%, 4%, 5%, preferably 2-3%;

[0015] Preferably, the supporting electrolyte is an inorganic phosphate, preferably one or more of sodium phosphate, potassium phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate or potassium dihydrogen phosphate. Its mass percentage in the electrolyte raw material solution is 5-15%, preferably 7-10%;

[0016] In the preparation method of the present invention, the electrolysis reaction is carried out in a diaphragmless electrolytic cell, and the electrolytic cell comprises an anode electrode and a cathode electrode;

[0017] Preferably, the cathode electrode in step S2 is a graphite electrode or a carbon steel electrode, preferably a graphite electrode or a carbon steel electrode with a Bi-Cd and / or Bi-Pb composite coating on the surface.

[0018] Preferably, the Bi-Cd or Bi-Pb composite coating has a thickness of 50-300 μm, such as 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, preferably 100-200 mm;

[0019] Preferably, in the Bi-Cd or Bi-Pb composite coating, the mass ratio of Bi to Cd or Pb is 1:5-30, preferably 1:10-20.

[0020] In the present invention, there is no special requirement for the shape and size of the electrode material. For example, in some examples, circular, rectangular, diamond and other shapes may be used; the size may be 3×3-5×5 cm.

[0021] Preferably, the method for preparing the cathode electrode comprises the following steps:

[0022] 1) preparing an electroplating solution, comprising the following raw materials in mass fractions: bismuth acetate 2-5%, such as 2.5%, 3%, 3.5%, 4%, 4.5%, cadmium chloride and / or lead fluoroborate 6-8%, such as 6.3%, 6.7%, 7.1%, 7.6%, 7.9%, EDTA 5-8%, such as 5.5%, 6%, 6.5%, 7%, 7.5%, boric acid 4-6%, such as 4.3%, 4.6%, 4.9%, 5.2%, 5.7%, saccharin 0.1-0.3%, such as 0.14%, 0.18%, 0.22%, 0.26%, ammonium chloride 8-12%, such as 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 2-aminopyridine-3-carboxamide 0.4-1.2%, such as 0.5%, 0.8%, 1.1%;

[0023] 2) The graphite material or carbon steel material is polished and then added to the electroplating solution of step 1), and a Bi-Cd or Bi-Pb composite coating is electroplated on the surface of the graphite electrode by electrochemical deposition to obtain an electrode material.

[0024] In step 1) of the present invention, the electroplating solution preferably comprises the following raw materials in mass fractions: 3-4% bismuth acetate, 7-8% cadmium chloride and / or lead fluoroborate, 6-7% EDTA, 5-6% boric acid, 0.2-0.25% saccharin, 9-10% ammonium chloride, and 0.8-1.0% 2-aminopyridine-3-carboxamide;

[0025] In step 1) of the present invention, the electroplating solution uses water as solvent.

[0026] In step 2) of the present invention, the polishing treatment has a polishing degree Ra of 0.2-0.5 μm, such as 0.45 μm, 0.35 μm, 0.25 μm, preferably 0.3-0.4 μm.

[0027] In step 2) of the present invention, the temperature of the electroplating solution is 30-50°C, such as 33°C, 36°C, 38°C, 42°C, 45°C, preferably 35-40°C.

[0028] In step 2) of the present invention, the electrochemical deposition method adopts a constant current electrochemical deposition method, and the current density used is 3-10A / cm 2 , for example 3.5A / cm 2 , 4.5A / cm 2 , 5.5A / cm 2 、6.5A / cm 2 , 7.5A / cm 2 , 9.5A / m 2 , preferably 5-8A / cm 2 ; The electrolysis time is 0.5-3h, for example 0.8h, 14h, 1.8h, 2.5h, preferably 1-2h;

[0029] Preferably, in the constant current electrochemical deposition method, the polished graphite material or carbon steel material is used as the cathode, and the graphite sheet is used as the anode, which are respectively connected to the negative electrode and the positive electrode of a DC power supply, and the distance between the two electrodes is 0.5-2.5 cm, for example, 0.8 cm, 1.2 cm, 1.6 cm, 1.8 cm, 2.2 cm, preferably 1.5-2.0 cm.

[0030] Preferably, the anode electrode is a platinum electrode, a carbon steel electrode or a DSA electrode, and the DSA electrode is preferably any one of Ti-based PbO2, IrO2, RuO2 or tin antimony oxide electrodes;

[0031] In step S2 of the preparation method of the present invention, the electrolytic reaction, the electrolytic cell voltage is 3-7V, preferably 4-5V; the electrolytic current density is 1000-2000A / m 2 , for example 1200A / m 2 、1400A / m 2 、1500A / m 2 、1600A / m 2 、1700A / m 2 、1800A / m 2 、1900A / m 2 、2000A / m 2 , preferably 1600-1800A / m 2 ;

[0032] In the electrolysis reaction, the electrolyte temperature is 20-50°C, such as 30°C, 35°C, 40°C, 45°C, 50°C, preferably 30-40°C; the electrolysis time is 5-20h, such as 5h, 10h, 15h, 20h, preferably 10-15h.

[0033] In step S2 of the preparation method of the present invention, the rate of adding acrylonitrile in the electrolysis reaction is related to the current density and the cathode area. Preferably, the rate of adding acrylonitrile (g / h) = 2.5*current density (A / cm2 )*Cathode area (cm 2 ), that is, at a current of 1A, 2.5g of acrylonitrile is added in 1h.

[0034] In step S2 of the preparation method of the present invention, after the electrolytic reaction is completed, purified adiponitrile can be obtained through post-treatment processes such as phase separation, extraction, and rectification. The operations included in the post-treatment process are all conventional methods in the art, and no specific requirements are made, and all achievable methods are acceptable. For example, the reaction liquid can be phase-separated to obtain an oil phase, and metal ions in the oil phase can be extracted with water, and then the adiponitrile product can be obtained by passing through a light removal tower and a heavy removal tower.

[0035] Preferably, the electrolytic cell is made of PP, PTFE and titanium, preferably titanium.

[0036] In the study of preparing adiponitrile from acrylonitrile electrochemical method, the inventor unexpectedly found that, compared with the prior art, after doping the surface of cadmium electrode or lead electrode with Bi element, not only the selectivity of dimerization of acrylonitrile to adiponitrile can be improved, the occurrence of side reactions can be reduced, and the addition of Bi in the coating can effectively increase the hardness and strength of the coating, reduce the loss rate of cadmium or lead on the cathode surface, and increase the life of the electrode. In addition, the present invention adds lauramide and its derivatives as cathode corrosion inhibitors in the electrolyte, which can effectively inhibit the corrosion of bismuth, lead and cadmium on the cathode surface, solve the problem that lead and cadmium in the traditional synthesis process quickly corrode and fall off on the cathode surface, and the electrolytic cell needs to be frequently replaced during the production process, and also has the advantages of simple process and low energy consumption, and is suitable for a wide range of industrial applications. DETAILED DESCRIPTION

[0037] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0038] The sources of the reagent raw materials used in the examples and comparative examples of the present invention are as follows:

[0039] Graphite materials, Hebei Heiqiang Carbon New Materials Co., Ltd.;

[0040] Bismuth acetate, Aladdin Reagents Ltd., ≥98%;

[0041] Lead tetrafluoroborate, Aladdin Reagent Co., Ltd., 50% in water;

[0042] Acrylonitrile, Aladdin Reagent Co., Ltd., 99%, containing inhibitor MEHQ;

[0043] Boric acid, Aladdin Reagent Co., Ltd., AR, ≥99.5%;

[0044] Ethylenediaminetetraacetic acid, Aladdin Reagent Co., Ltd., purity ≥98%;

[0045] N-[3-(Dimethylamino)propyl]lauramide, Aladdin Reagent Co., Ltd., ≥97%;

[0046] Potassium dihydrogen phosphate, Aladdin Reagent Co., Ltd., purity> 99.5%;

[0047] Tetramethylammonium hydroxide, Aladdin Reagent Co., Ltd., AR, 25% aqueous solution;

[0048] Cadmium chloride, Aladdin Reagent Co., Ltd., purity> 99%;

[0049] Platinum-titanium electrode, Xi’an Taijin Co., Ltd., coating thickness 1 μm;

[0050] Ti-based IrO2 anode, Jiangsu Yianteng Special Electrode Co., Ltd., iridium titanium mesh 50×100;

[0051] Ti-based PbO2 anode, Jiangsu Yianteng Special Electrode Co., Ltd., lead-titanium mesh 50×100;

[0052] Ti-based RuO2 anode, Jiangsu Yianteng Special Electrode Co., Ltd., ruthenium titanium mesh 50×100;

[0053] Unless otherwise specified, other raw materials or reagents were purchased from commercial sources.

[0054] Diaphragmless electrolytic cell: Jiangyin Tianyuan Electrochemical Equipment Co., Ltd., box-type diaphragmless small-scale electrolytic cell, made of titanium.

[0055] The test methods used in the embodiments and comparative examples of the present invention are as follows:

[0056] In the following examples, adiponitrile was characterized by hydrogen spectrum using a nuclear magnetic resonance spectrometer (Brucker ARX-400);

[0057] In the following examples, the conversion and selectivity of adiponitrile were determined by gas chromatographic area correction normalization analysis. The chromatographic analysis conditions were as follows:

[0058] Instrument model: Shimadzu GC2010; chromatographic column: HP-INNOWAX quartz capillary column (30m×0.25mm×0.25μm); column temperature: programmed temperature rise (initial temperature 40℃, maintained for 2min, increased to 180℃ at 20℃ / min, and then increased to 220℃ at 5℃ / min); inlet temperature: 310℃; FID temperature: 300℃; N2 flow rate: 1mL / min; H2 flow rate: 40mL / min; septum purge (N2) flow rate: 3mL / min; carrier gas (N2) flow rate: 1mL / min; split injection, split ratio: 50; injection volume: 0.1μL.

[0059] Adiponitrile selectivity = adiponitrile molar yield * 2 / acrylonitrile molar consumption * 100%

[0060] Current efficiency = adiponitrile molar yield * 2 * 96500 / (electrolysis current * electrolysis time) * 100%

[0061] Example 1

[0062] (1) Preparing an electrode material for electrolyzing acrylonitrile to synthesize adiponitrile, the steps are:

[0063] 1) 8 g of bismuth acetate, 16 g of lead tetrafluoroborate, 16 g of EDTA, 10 g of boric acid, 0.2 g of saccharin, 16 g of ammonium chloride, 0.8 g of 2-aminopyridine-3-carboxamide, and deionized water were mixed to prepare 200 g of electroplating solution;

[0064] 2) A 3×3 cm rectangular carbon steel material is polished to a polishing degree Ra of 0.5 μm, and then added to the electroplating solution of step 1), and the polished carbon steel material is used as a cathode electrode connected to the negative pole of a DC power supply, and a graphite sheet is used as an anode electrode connected to the positive pole of a DC power supply, and the distance between the two electrodes is 0.5 cm. By adopting a constant current electrochemical deposition method, the electroplating solution is kept at a constant temperature of 35° C., the current is 10 A, and the electrolysis time is 0.5 h, a carbon steel electrode coated with a Bi-Pb composite coating on the surface is obtained.

[0065] The thickness of the Bi-Pb composite coating on the electrode material surface is 50 μm; the mass ratio of Bi to Pb is 1:20

[0066] (2) electrolyzing acrylonitrile to synthesize adiponitrile, the steps are:

[0067] S1: 2 g acrylonitrile, 4 g tetramethylammonium hydroxide, 0.2 g EDTA, 4 g N-[3-(dimethylamino)propyl] lauramide, 10 g potassium phosphate and 179.8 g water were uniformly mixed to prepare 200 g electrolytic raw material solution, and then added into a diaphragmless electrolytic cell;

[0068] S2: The carbon steel electrode coated with the Bi-Pb composite coating prepared in step (1) is used as the cathode electrode, and the platinum electrode is used as the anode electrode; the electrolyte is heated to 20°C for electrolysis reaction, the electrolytic cell voltage is 7V, and the electrolysis current density is 2000A / m 2 At the same time, acrylonitrile is continuously added dropwise at a rate of 4.5 g / h. The electrolysis time is 5 hours. After the electrolysis reaction is completed, the reaction liquid is separated into oil phases, and the metal ions in the oil phase are extracted with water. Then, the oil phase is passed through a light removal tower and a heavy removal tower to obtain adiponectin product.

[0069] In this embodiment, the conversion rate of raw material acrylonitrile is 93.6%, the selectivity of synthesized adiponitrile is 91.5%, the loss rate of Pb on the cathode surface is 0.5 ppm / h, and the current efficiency is 95.3%.

[0070] Example 2

[0071] (1) Preparing an electrode material for electrolyzing acrylonitrile to synthesize adiponitrile, the steps are:

[0072] 1) 6 g of bismuth acetate, 12 g of cadmium chloride, 12 g of EDTA, 12 g of boric acid, 0.5 g of saccharin, 24 g of ammonium chloride, 1.6 g of 2-aminopyridine-3-carboxamide, and deionized water were mixed to prepare 200 g of electroplating solution;

[0073] 2) A 3×3 cm rectangular graphite material is polished to a polishing degree Ra of 0.2 μm, and then added to the electroplating solution of step 1), and the polished graphite material is used as a cathode electrode connected to the negative electrode of a DC power supply, and a graphite sheet is used as an anode electrode connected to the positive electrode of a DC power supply, and the distance between the two electrodes is 2 cm. By adopting a constant current electrochemical deposition method, the electroplating solution is kept at a constant temperature of 30° C., the current is 8 A, and the electrolysis time is 2 hours, a graphite electrode coated with a Bi-Cd composite coating on the surface is obtained.

[0074] The thickness of the Bi-Cd composite coating on the electrode material surface is 300 μm; the mass ratio of Bi to Cd is 1:10

[0075] (2) electrolyzing acrylonitrile to synthesize adiponitrile, the steps are:

[0076] S1: 1 g acrylonitrile, 2 g tetramethylammonium hydroxide, 1 g EDTA, 10 g lauramide, 14 g dipotassium hydrogen phosphate and 172 g water were uniformly mixed to prepare 200 g electrolytic raw material solution, and then added into a diaphragmless electrolytic cell;

[0077] S2: The graphite electrode coated with the Bi-Cd composite coating prepared in the above step (1) is used as the cathode electrode, and the carbon steel electrode is used as the anode electrode; the electrolyte is heated to 30°C for electrolysis reaction, the electrolytic cell voltage is 4V, and the electrolysis current density is 1800A / m 2 At the same time, acrylonitrile is continuously added dropwise at a rate of 4.05 g / h. The electrolysis time is 10 hours. After the electrolysis reaction is completed, the reaction liquid is separated into oil phases, and the metal ions in the oil phase are extracted with water. Then, the oil phase is passed through a light removal tower and a heavy removal tower to obtain adiponectin product.

[0078] In this embodiment, the conversion rate of raw material acrylonitrile is 94.8%, the selectivity of synthesized adiponitrile is 90.9%, the loss rate of Cd on the cathode surface is 0.4 ppm / h, and the current efficiency is 93.4%.

[0079] Example 3

[0080] (1) Preparing an electrode material for electrolyzing acrylonitrile to synthesize adiponitrile, the steps are:

[0081] 1) 10 g of bismuth acetate, 14 g of cadmium chloride, 10 g of EDTA, 8 g of boric acid, 0.4 g of saccharin, 18 g of ammonium chloride, 2 g of 2-aminopyridine-3-carboxamide, and deionized water were mixed to prepare 200 g of electroplating solution;

[0082] 2) A 3×3 cm rectangular carbon steel material is polished to a polishing degree Ra of 0.4 μm, and then added to the electroplating solution of step 1), and the polished carbon steel material is used as a cathode electrode connected to the negative pole of a DC power supply, and a graphite sheet is used as an anode electrode connected to the positive pole of a DC power supply, and the distance between the two electrodes is 1.5 cm. By adopting a constant current electrochemical deposition method, the electroplating solution is kept at a constant temperature of 40° C., the current is 5 A, and the electrolysis time is 1 hour, a carbon steel electrode coated with a Bi-Cd composite coating on the surface is obtained.

[0083] The thickness of the Bi-Cd composite coating on the electrode material surface is 100 μm; the mass ratio of Bi to Cd is 1:5

[0084] (2) electrolyzing acrylonitrile to synthesize adiponitrile, the steps are:

[0085] S1: 6 g acrylonitrile, 6 g tetramethylammonium hydroxide, 2 g EDTA, 6 g N, N-diethyl lauramide, 20 g potassium dihydrogen phosphate and 160 g water were uniformly mixed to prepare 200 g electrolytic raw material solution, and then added into the diaphragmless electrolytic cell;

[0086] S2: The carbon steel electrode coated with the Bi-Cd composite coating prepared in step (1) is used as the cathode electrode, and the carbon steel electrode is used as the anode electrode; the electrolyte is heated to 40°C for electrolysis reaction, the electrolytic cell voltage is 5V, and the electrolysis current density is 1600A / m 2 At the same time, acrylonitrile is continuously added at a rate of 3.6 g / h. The electrolysis time is 15 hours. After the electrolysis reaction is completed, the reaction liquid is separated into oil phases, and the metal ions in the oil phase are extracted with water. Then, the oil phase is passed through a light removal tower and a heavy removal tower to obtain adiponectin product.

[0087] In this embodiment, the conversion rate of raw material acrylonitrile is 95.1%, the selectivity of synthesized adiponitrile is 90.4%, the loss rate of Cd on the cathode surface is 0.5 ppm / h, and the current efficiency is 92.7%.

[0088] Example 4

[0089] (1) Preparing an electrode material for electrolyzing acrylonitrile to synthesize adiponitrile, the steps are:

[0090] 1) 4 g of bismuth acetate, 16 g of cadmium chloride, 14 g of EDTA, 8 g of boric acid, 0.6 g of saccharin, 20 g of ammonium chloride, 2.4 g of 2-aminopyridine-3-carboxamide, and deionized water were mixed to prepare 200 g of electroplating solution;

[0091] 2) A 3×3 cm rectangular carbon steel material is polished to a polishing degree Ra of 0.3 μm, and then added to the electroplating solution of step 1), and the polished carbon steel material is used as a cathode electrode connected to the negative pole of a DC power supply, and a graphite sheet is used as an anode electrode connected to the positive pole of a DC power supply, and the distance between the two electrodes is 2.5 cm. By adopting a constant current electrochemical deposition method, the electroplating solution is kept at a constant temperature of 50° C., the current is 3A, and the electrolysis time is 3 hours, a carbon steel electrode coated with a Bi-Cd composite coating on the surface is obtained.

[0092] The thickness of the Bi-Cd composite coating on the electrode material surface is 200 μm; the mass ratio of Bi to Cd is 1:30

[0093] (2) electrolyzing acrylonitrile to synthesize adiponitrile, the steps are:

[0094] S1: 10 g acrylonitrile, 1 g tetramethylammonium hydroxide, 0.6 g EDTA, 2 g N-[3-(dimethylamino)propyl]lauramide, 30 g sodium dihydrogen phosphate and 156.4 g water were uniformly mixed to prepare 200 g electrolytic raw material solution, and then added into a diaphragmless electrolytic cell;

[0095] S2: The carbon steel electrode coated with the Bi-Cd composite coating prepared in step (1) is used as the cathode electrode, and the carbon steel electrode is used as the anode electrode; the electrolyte is heated to 50°C for electrolysis reaction, the electrolytic cell voltage is 3V, and the electrolysis current density is 1000A / m 2 At the same time, acrylonitrile is continuously added dropwise at a rate of 2.25 g / h. The electrolysis time is 10 hours. After the electrolysis reaction is completed, the reaction liquid is separated into oil phases, and the metal ions in the oil phase are extracted with water. Then, the oil phase is passed through a light removal tower and a heavy removal tower to obtain adiponectin product.

[0096] In this embodiment, the conversion rate of raw material acrylonitrile is 90.9%, the selectivity of synthesized adiponitrile is 93.7%, the loss rate of Cd on the cathode surface is 0.4 ppm / h, and the current efficiency is 94.1%.

[0097] Comparative Example 1

[0098] Referring to the method of Example 1, in step (2), no N-[3-(dimethylamino)propyl]lauramide is added to the electrolytic raw material solution, and other operations remain unchanged to obtain adiponectin product.

[0099] In this comparative example, the conversion rate of raw material acrylonitrile was 77.9%, the selectivity of synthesized adiponitrile was 82.1%, the loss rate of Cd on the cathode surface was 25.3 ppm / h, and the current efficiency was 81.1%.

Claims

1. An electrochemical preparation method of adiponitrile, characterized in that: The method is carried out in a diaphragmless electrolyzer, and the steps include: S1: uniformly mix acrylonitrile, quaternary ammonium base, EDTA, lauramide and its derivatives, supporting electrolyte and water to prepare an electrolytic raw material solution, and inject it into the electrolytic cell; S2: Pass current into the electrolytic cell to carry out electrolysis reaction.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass percentage of acrylonitrile in the electrolytic raw material solution is 0.5-5%, preferably 1-3%; Preferably, the quaternary ammonium base is one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide, and its mass percentage in the electrolytic raw material solution is 0.5-3%, preferably 1-2%; Preferably, the mass percentage of EDTA in the electrolytic raw material solution is 0.1-1%, preferably 0.3-0.5%; Preferably, the lauramide and its derivatives include one or more of lauramide, N-[3-(dimethylamino)propyl]lauramide, and N,N-diethyllauramide; Preferably, the mass percentage of lauramide and its derivatives in the electrolyte raw material solution is 1-5%, preferably 2-3%; Preferably, the supporting electrolyte is an inorganic phosphate, preferably one or more of sodium phosphate, potassium phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate or potassium dihydrogen phosphate; and its mass percentage in the electrolytic raw material solution is 5-15%, preferably 7-10%.

3. The preparation method according to claim 1 or 2, characterized in that: The electrolysis reaction is carried out in a diaphragmless electrolytic cell, which comprises an anode electrode and a cathode electrode.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step S2, the cathode electrode is a graphite electrode or a carbon steel electrode, preferably a graphite electrode or a carbon steel electrode coated with a Bi-Cd and / or Bi-Pb composite coating on the surface; The Bi-Cd or Bi-Pb composite coating has a thickness of 50-300 μm, preferably 100-200 mm; Preferably, in the Bi-Cd or Bi-Pb composite coating, the mass ratio of Bi to Cd or Pb is 1:5-30, preferably 1:10-20; Preferably, the anode electrode is a platinum electrode, a carbon steel electrode or a DSA electrode; Preferably, the DSA electrode is any one or more of Ti-based PbO2, IrO2, RuO2 or tin antimony oxide electrodes.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method of a graphite electrode or a carbon steel electrode having a surface coated with a Bi-Cd and / or Bi-Pb composite coating comprises the following steps: 1) preparing an electroplating solution, comprising the following raw materials in mass fractions: 2-5% bismuth acetate, 6-8% cadmium chloride and / or lead fluoroborate, 5-8% EDTA, 4-6% boric acid, 0.1-0.3% saccharin, 8-12% ammonium chloride, and 0.4-1.2% 2-aminopyridine-3-carboxamide; 2) The graphite material or carbon steel material is polished and then added to the electroplating solution of step 1), and a Bi-Cd or Bi-Pb composite coating is electroplated on the surface of the graphite electrode by electrochemical deposition to obtain an electrode material.

6. The preparation method according to claim 5, characterized in that: In step 1), the electroplating solution preferably comprises the following raw materials in mass fractions: 3-4% bismuth acetate, 7-8% cadmium chloride and / or lead fluoroborate, 6-7% EDTA, 5-6% boric acid, 0.2-0.25% saccharin, 9-10% ammonium chloride, and 0.8-1.0% 2-aminopyridine-3-carboxamide; Preferably, in step 1), the electroplating solution uses water as solvent.

7. The preparation method according to claim 5 or 6, characterized in that: The polishing treatment has a polishing degree Ra of 0.2-0.5 μm, preferably 0.3-0.4 μm; Preferably, in step 2), the temperature of the electroplating solution is 30-50°C, preferably 35-40°C; Preferably, in step 2), the electrochemical deposition method adopts a constant current electrochemical deposition method, and the current density used is 3-10A / cm 2 , preferably 5-8A / cm 2 ; The electrolysis time is 0.5-3h, preferably 1-2h; Preferably, in the constant current electrochemical deposition method, the polished graphite material or carbon steel material is used as the cathode, and the graphite sheet is used as the anode, which are respectively connected to the negative electrode and the positive electrode of a DC power supply, and the distance between the two electrodes is 0.5-2.5 cm, preferably 1.5-2.0 cm.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In step S2, acrylonitrile is added to the electrolytic cell to maintain the acrylonitrile concentration in the electrolyte; Preferably, the acrylonitrile addition rate (g / h) = 2.5*current density (A / cm 2 )*Cathode area (cm 2 ).

9. The preparation method according to any one of claims 1 to 8, characterized in that: In step S2, the electrolysis reaction is carried out at an electrolytic cell voltage of 3-7 V, preferably 4-5 V; and an electrolysis current density of 1000-2000 A / m 2 , preferably 1600-1800A / m 2 ; Preferably, in the electrolysis reaction, the electrolyte temperature is 20-50°C, preferably 30-40°C; the electrolysis time is 5-20h, preferably 10-15h; Preferably, the material of the electrolytic cell is PP, PTFE and titanium, preferably titanium.

Citation Information

Patent Citations

  • Electrolyte and method for preparing adiponitrile by electrolytic acrylonitrile dimerization

    CN108517536A

  • electrolytic hydrodimerization process

    FR1491516A